Relationship Lending and Employment Decisions in Firms’ Bad Times - Murro, Pierluigi; Oliviero, Tommaso; Zazzaro, Alberto (Journal of Financial and Quantitative Analysis, 2023)
Abstract Using firm-level survey information, we investigate whether relationship lending affects firms’ employment decisions in the face of negative sales shock. We find that firms with a durable relationship with their main bank display significantly less employment growth sensitivity to such shocks, especially where these are transitory. The result is stronger for younger and smaller firms that benefit from tighter bank-firm relationships, and for firms in sectors or economic environments where the costs of employment adjustment are greater. Our findings indicate that relationship lending provides liquidity insurance to firms to meet their demand for labor hoarding.